The Role of 18F-FDG PET/CT in the Management of the Autoimmune Thyroid Diseases - Małkowski, Bogdan; Serafin, Zbigniew; Glonek, Rafał; Suwała, Szymon; Łopatto, Rita; Junik, Roman (Frontiers in Endocrinology, 2019)
Objective: It is a well-known fact that positron emission tomography (PET) is an effective tool in the assessment of thyroid focal lesions, however only few studies so far have investigated its role in monitoring of autoimmune thyroid diseases (AITDs). The aim of this study is to assess if PET scan may be useful for the assessment of the thyroid gland in patients with an AITD - Hashimoto's thyroiditis. Methods: We evaluated twenty subjects with diagnosed Hashimoto's thyroiditis (proven by presence of elevated thyroid antibodies level and by thyroid imaging). The maximum standardized uptake value (SUV-max) of the thyroid parenchyma was measured using 18F-FDG-PET/CT. Control group consisted of patients who have been in carcinoma remission for other reasons than thyroid cancer and who had been investigated by PET scan to exclude carcinoma recurrence. All control group subjects had their thyroid glands intact, none of them had a medical history of thyroid disease including thyroid nodules. AITDs had been excluded in all control group subjects. STATISTICA 13.1 software was used for statistical analysis. Results: Results: The SUV-max was significantly higher in patients with an AITD than in healthy subjects (median SUV-max 3.94 vs 1.95; p=0.005). Conclusions: 18F-FDG-PET/CT scan may differentiate normal thyroid parenchyma from the diffused inflammatory changes of the thyroid gland in patients with AITDs. However, the researches must be continued. Keywords: thyroid, ultrasound, autoimmune thyroid disease, 18FDG-PET, Hashimoto’s disease